Local organic food: The social implications of sustainable consumption - Gill Seyfang (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2004)
In recent years organically-grown produce for local markets has become more popular with consumers, and re-localising food chains has been put forward as a strategy for sustainable consumption due to the apparent benefits to local economies, communities, and environments. Notions of 'sustainable consumption' are contested, however, and can represent competing ideologies and perspectives about the environment and society. In order to examine the social implications of sustainable consumption, this paper sets out an analytical framework based upon Cultural Theory to typologise and categorise the range of perspectives on sustainable consumption into 'hierarchical', 'individualistic' and 'egalitarian' worldviews. It goes on to consider how these various worldviews might promote locally-grown organic food as a sustainable consumption initiative, and illustrates the social implications of each model and the tensions between them. These tensions are evident when attention is turned to a case study of Eostre Organics, a local organic food producers cooperative in Norfolk, East Anglia. Research with both Eostre's producers and consumers reveals that the values embedded in its practice are both partisan and pluralistic. Identifying Eostre as an 'egalitarian' endeavour, its interactions with policy regimes and social and economic institutions are examined, in order to understand the barriers it faces in operation and the institutional factors inhibiting the growth of sustainable food initiatives of this kind. These include public acceptability, externalisation of environmental costs associated with conventional produce, and a public sector which does not do enough to actively promote the use of locally sourced food. In addition to addressing these barriers, the implications of these findings for sustainable consumption policy and practice are that governments should recognise the contribution made by 'egalitarian' initiatives, and create policy space to let these grassroots projects thrive and develop 'bottom-up' responses to sustainable consumption.
Keywords: 330; institutions; local food; localisation; organics; sustainable consumption; Biokost; Alternative Ökonomie; Tauschwirtschaft; Nachhaltige Entwicklung; Einkaufsgenossenschaft